Context aware privacy in visual surveillance - Moncrieff, Simon; Venkatesh, Svetha; West, Geoff (IAPR, 2008)
In this paper we present preliminary work implementing dynamic privacy in public surveillance. The aim is to maximise the privacy of those under surveillance, while giving an observer access to sufficient information to perform their duties. As these aspects are in conflict, a dynamic approach to privacy is required to balance the systempsilas purpose with the systempsilas privacy. Dynamic privacy is achieved by accounting for the situation, or context, within the environment. The context is determined by a number of visual features that are combined and then used to determine an appropriate level of privacy.